The effect of concentrate supplementation on nutrient flow to the omasum in dairy cows receiving freshly cut grass - Sairanen, Auvo; Khalili, Hannele; Nousiainen, Jouni I; Ahvenjärvi, Seppo; Huhtanen, Pekka (American dairy science association, 2005)
An experiment was carried out to determine the effect of increasing the amount of grain-based concentrate (0, 3, or 6 kg/d) on nutrient flow to the omasum, rumen fermentation pattern, milk yield, and nutrient use of dairy cows. Harvested timothy-meadow fescue grass was fed individually 3 times daily to 6 rumen-cannulated Holstein-Friesian cows in a duplicated 3 x 3 Latin square experiment. Grass was offered as 6 equal meals daily, and concentrates was fed as 2 equal meals daily. Nitrogen, microbial N, and neutral detergent fiber (NDF) flow from the rumen were measured using an omasal sampling technique in combination with a triple marker method [CoEDTA, Yb and indigestible NDF (INDF) as markers]. Concentrate supplementation linearly decreased ruminal pH, N degradability, ammonia N concentration, and molar proportion of acetate and increased the molar proportion of butyrate. Supplementation of grass with concentrates linearly increased dry matter intake (DMI), microbial N synthesis, N, and NDF flow to the omasum, and ruminal and total tract NDF digestibility decreased linearly. Decreases in NDF digestibility in response to concentrates was primarily related to a decrease in the rate of digestion. lncreased DMI overcame the negative effects of concentrate on NDF digestion, resulting in a linear increase in total metabolizable energy (ME) intake and milk production. Physical constraints were found not to limit grass DMI. Concentrate supplementation increased the apparent use of dietary N for milk production because of a reduction in N intake, rather than thorough improvements in N capture in the rumen.
Keywords: Ko; lypsykarja; nautakarja; heinä; väkirehut; rehut; ruokinta; dairy cattle; dairy cows; hay; concentrates; feeds; feeding; grass; nutrient flow